Analysis of macula structural changes in Moyamoya disease using AI-assisted OCT - Xiaochun Li; Guangfeng Liu; Yuan Ni; Dan Song; Fei Yang; Xijuan Wang; Yaqian Niu; Chengxia Zhang; Yan Zhang (Photodiagnosis and Photodynamic Therapy)
Objective: To investigate macula structure thickness and volume changes in patients with moyamoya disease (MMD). Method: In this cross-sectional study, we used artificial intelligence (AI) -assisted optical coherence tomography (OCT) to analyze the thickness and volume of macula in Moyamoya patients. ETDRS zoning divides the macula into nine different regions. In 15 patients with radial scanning OCT, the average thickness and volume of retina, RNFL, GCL, and choroid in these regions were measured. In 30 patients with radial or horizontal scanning OCT, based on the anatomical structure, the macula is divided into seven segments. Mean Sattler layer–choriocapillaris complex thickness (SLCCT), Haller layer thickness, and total choroidal thickness were measured for each segment using AI-assisted OCT. Results: We recruited 30 patients (59 eyes) with MMD. In the 15 patients (29 eyes) who underwent radial scanning OCT, no significant change in retina, RNFL, GCL, and choroidal thickness was identified between the two groups (p > 0.05). There was no significant change in retina, RNFL, or choroidal volume between the two groups in different ETDRS macula regions (p > 0.05). The GCL volume in the macula's inner ring nasal portion (IN) was significantly lower. SLCCTs were considerably reduced in six macula regions in moyamoya groups (p < 0.05). There was no statistically significant change in Haller layer thickness. Only the nasal perifovea (PE_N) exhibited a significant variation in choroidal thickness. The Moyamoya group showed reduced choroidal thickness in PE_N segment. Conclusion: In patients with MMD, there is thinning of the Sattler layer–choriocapillaris complex in the choroid.